Low-Carbon Literacy Profile of Senior High School Students in Indonesia: Implications for Future Climate Change Mitigation - Qumariyatul Intani; Eko Yuliyanto; Eny Winaryati; Rica Mae Guarin (Jurnal VARIDIKA, 2024)
Climate change represents a critical global challenge with profound impacts on human societies. One prominent strategy to mitigate its effects involves fostering low-carbon behavior, often termed low-carbon literacy. Although prior research has investigated various aspects of low-carbon literacy, there has been limited focus on high school students in Central Java, a region acutely impacted by climate change. This study evaluates the low-carbon literacy of high school students in Central Java, Indonesia. Using a validated survey instrument, the research measured three primary domains: knowledge, attitudes, and behaviors, through 31 items. The study sampled 400 high school students, revealing an overall literacy score of 4.3 out of 5 across these domains. Despite the relatively high average score, each domain exhibited specific deficiencies, underscoring the necessity to enhance low-carbon literacy further. A significant limitation of this study is the instrument's contextual specificity to Central Java, which calls for the development of more comprehensive assessment tools and the inclusion of a more geographically diverse sample in future investigations.